Efficiency of Diagnostics and Surgical Treatment of Primary Benigh Heart Tumors - R. M. Vitovsky; V. V. Isaenko; E. A. Belinsky; A. A. Pischurin; O. Z. Paratsiy; E. V. Satmari; T. I. Dedkova; I. G. Yakovenko; I. V. Martyshchenko; L. G. Matiushko; V. M. Rjabitsa; N. I. Volkova (Ukrainian Journal of Cardiovascular Surgery, 2016)
In N. M. Amosov Institute of Cardio-Vascular surgery of the Academy of Medical Sciences of Ukraine for period from 1.01.1969 to 1.01.2016 868 patients with primary heart tumors had surgical treatment. The myxomas of heart (MH) was found in 778 (89,6%), from them in 680 (87,3%) cases – MH of left atrium (LA). The other benign heart tumours were observed in 32 (3,7%) cases, malignant heart tumours – in 58 (6,7%). Hospital mortality was 5% (39 cases). In the last 15 years a 415 operation were executed without lethal results.